Baseline features of the AMYPAD Diagnostic and Patient Management Study (DPMS) participants: Neuroimaging / differential diagnosis. (7th December 2020) - Altomare, Daniele; Collij, Lyduine; Garibotto, Valentina; Poitrine, Léa; Moro, Christian; Alves, Isadora Lopes; van Maurik, Ingrid S.; Berkhof, Johannes; Scheltens, Philip; Delrieu, Julien; Molinuevo, Jose Luis; Nordberg, Agneta K; et al.
Abstract: Background: AMYPAD‐DPMS is the largest European, multicenter, prospective and randomized study assessing clinical utility and cost‐effectiveness of amyloid‐PET in a controlled but realistic clinical setting. In the present abstract we report preliminary results on the baseline features of the first study participants. Method: A total of 900 participants (300 with subjective cognitive decline plus [SCD+], 300 with mild cognitive impairment [MCI], and 300 with dementia) will be enrolled and randomized into 3 study arms: ARM‐1, amyloid‐PET performed early in the diagnostic workup; ARM‐2, amyloid‐PET performed late in the diagnostic work‐up; and ARM‐3, amyloid‐PET performed if and when the physician chooses to. Result: As of January 23 rd 2020, 617 participants (154 SCD+, 303 MCI, and 160 dementia) have been enrolled from 8 centers. Baseline features are reported in Table 1. SCD+ participants are younger than MCI ( p =0.006) and dementia ( p <0.001) participants. SCD+ are more highly educated than MCI and dementia ( p <0.001), and MCI are more highly educated that dementia ( p =0.008). As expected, worse global cognition is observed in dementia ( p <0.001) compared to MCI and SCD+, and in MCI compared to SCD+ ( p <0.001). Among those who already underwent amyloid‐PET, 34% (30/88) of SCD+, 58% (90/155) of MCI, and 74% (60/81) of dementia patients were amyloid‐positive based on visual PET scan assessment. Conclusion: The socio‐demographic and cognitive features of the first 68% of AMYPAD‐DPMS participants are as expected for a memory clinic population, confirming the inclusion/exclusion criteria resulted in a representative sample. These results support the generalizability of the final study results. The end of participants' enrolment is expected by mid‐2020.